Generation Y Behavior Change In Bandung City In Receiving News Covid-19 - Giraldi Prama Yudistira; Asaas Putra (Institute of Computer Science (IOCS), 2022)
The city of Bandung has significant changes that are also felt by its people, especially the people in the Y generation group who are so many in the city of Bandung. This change in behavior is caused by the large reception of Covid-19 news on the internet and the high use of the internet in the city of Bandung. this study aims to determine the change in behavior in generation y in the city of Bandung in receiving news of covid-19 on the internet. The research method used is a descriptive qualitative method. The theory used is the communication theory of Behaviorism developed by Jhon B. Watson (1878-1958). The results of this study state that the changes in behavior that occur are very diverse, namely, changes in behavior to individuals who always use cashless payments, changes in work styles, namely more dominant working WFH (Work From Home), significant changes in healthy lifestyles, changes in behavior to not being used to spending too long outside the home, behaving more calmly in facing situations and conditions, behavior change becomes concerned about the development of the pandemic, caring about himself and his surroundings. Researchers concluded that Generation Y in Bandung City has very diverse behavior changes.